Variation in origin of pectoralis minor muscle: a case report - Agrawal, Soujanya; Singroha, Ritu; Garsa, Vipin; Rathee, Suresh K.; Sran, Sukhdeep (International Journal of Research in Medical Sciences, 2025)
Pectoralis minor is a slender, triangular muscle deep within the pectoralis major. It originates from the exterior surfaces of the third through fifth ribs, in the vicinity of their cartilages and fascia covering the adjacent external intercostal muscles. Under the pectoralis major's cover, its fibres climb laterally and converge into a flat tendon linked to the medial border and top surface of the scapula's coracoid process. A portion of the tendon may cross the coracoid process and enter the coracoacromial ligament. In regular dissection muscles of the pectoral region were observed and the pectoralis minor muscle variation was noted. Out of 10 cadavers, a male cadaver showed bilateral variation in the origin of the pectoralis minor muscle. In this case, we found the origin of the pectoralis minor muscle was from the outer surface of the second to fifth rib, near their cartilages. The present case is a rare anomaly and is being reported as this knowledge is of importance great importance to surgeons, orthopedics and sports medicine as it could lead to shoulder pain, rotator cuff pathologies, winging of scapula, impingement of neurovascular bundle knows as pectoralis minor syndrome.